1979
DOI: 10.1159/000122886
|View full text |Cite
|
Sign up to set email alerts
|

<i>In vitro</i> Regulation of ACTH Release from Neurointermediate Lobe of Rat Hypophysis

Abstract: The effect of various neurotransmitters on adrenocorticotropic hormone (ACTH) release from superfused neurointermediate lobes of rat hypophysis (NIL) was investigated. Acetylcholine, serotonin, and histamine were shown to have no significant effect on the spontaneous release of ACTH. In contrast, dopamine (DA) and noradrenaline (NA) stimulated NIL ACTH release in a dose-dependent manner. The stimulating effect of DA was mimicked by apomorphine and inhibited by haloperidol, whereas that of NA was abolished by p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
11
0

Year Published

1981
1981
1998
1998

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 8 publications
6
11
0
Order By: Relevance
“…Both DA and apomorphine (10-12, lO'13 M) were found to stimulate the release of bioac tive ACTH from perfused rat NILs [4] in a manner similar to the DA-induced stimulation of prolactin (PRL) release from rat anterior pituitary cells by low concentrations of DA [ 12]. Both effects were blocked by haloperidol which led to the proposal [12] that the dopaminergic control of PRL release involves both a stimulatory and an inhibitory DA receptor.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Both DA and apomorphine (10-12, lO'13 M) were found to stimulate the release of bioac tive ACTH from perfused rat NILs [4] in a manner similar to the DA-induced stimulation of prolactin (PRL) release from rat anterior pituitary cells by low concentrations of DA [ 12]. Both effects were blocked by haloperidol which led to the proposal [12] that the dopaminergic control of PRL release involves both a stimulatory and an inhibitory DA receptor.…”
Section: Discussionmentioning
confidence: 93%
“…Despite the generally accepted inhibitory effect of DA on the PI, recent studies have indicated a stimulatory role for this catecholamine [4]. Both DA and apomorphine (10-12, lO'13 M) were found to stimulate the release of bioac tive ACTH from perfused rat NILs [4] in a manner similar to the DA-induced stimulation of prolactin (PRL) release from rat anterior pituitary cells by low concentrations of DA [ 12].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In rats, such a dichotomy in the control of the release of a pep tide present in both AP and N-IL has been previously docu mented for adrenocorticotropin (ACTH) and a-melanocyte stimulating hormone (aMSH) [15,46], which are both de rived from the same common precursor as p-EP [30, 32, 38]. Recent evidence suggests that, when animals are acutely stressed, changes in AP ACTH levels involve the hypothalamo-pituitary-adrenal axis [24, 26, 40]; in contrast, changes in N-IL aMSH levels (and those of N-IL ACTH, where de termined) appear under the control of an aminergic system, presumably related to that present in the median eminence [6,17, 37], However, in rats, it has not been determined whether PEP and/or PLPH present in AP, N-IL and hypo thalamus (HT) behave in a parallel manner to that of ACTH and aMSH under similar conditions. …”
mentioning
confidence: 99%
“…At present, there is no clear evidence that 5-HT stimulates follicle-stimulating hormone (FSH) and thyroid-stimulating hormone (TSH) release. In contrast, the in vitro studies have failed to show a direct action of 5-HT on anterior pituitary (AP) cells [8, 9], although there are controversial data on ACTH release by AP cells [10, 11, 12]. The effect of 5-HT on α-melanocyte-stimulating hormone (αMSH) release by rat intermediate lobe (IL) is also controversial in vitro [13, 14], while in vivo clearly stimulates αMSH release, this action being probably mediated through inhibition of tuberohypophyseal dopaminergic neurons [15, 16].…”
Section: Introductionmentioning
confidence: 99%